Analysis of Preeclampsia in Pregnant Women Reviewing from Vascular Disorders due to Endothelial Dysfunction - Tutik Nushah; Yuly Peristiowati (STRADA : Jurnal Ilmiah Kesehatan, 2022)
Preeclampsia is a multisythemic disorder in pregnancy. Some theories reveal that PE is a result of imuune and hormonal response disorders during pregnancy. In the preeclampsia there is a endothelial dysfunction in the controlling vascular function to respond to blood composition and function disorder as a physical barrier to the exchange of fluid, ion proteins and cells from the blood through the vasculer wall. In addition, there is a decrease in angiogenesis and vasodilatation of blood vessels in response to oxygen pressure and mechanical stress like shear stress. Analyzing the incidence of preeclampsia in pregnant women in terms of vascular disorders doe to endothelial dysfunction. Design : observational, a cross sectional approach. Probability sampling using random sampling. Statistical analysis logistic regression. Data processing Hosmer and Lemeshow Test. Assumption of the amount of influence a summary model. PE incidence of pregnant woman 94 (6.15%), 53 people (56.4%) PE, 41 (43.6%) PEB.